Factors Influencing Quality of Life Among Older Persons Living With Osteoarthritis Using 3 Different Definitions - Sumaiyah, Mat; Ng, Chin Teck; Farhana, Fadzli; Faizatul, Izza Rozalli; Morgan, Karen; Tan, Maw Pin * (Lippincott, Williams & Wilkins, 2022)
Aim: While the impact of osteoarthritis (OA) on the older person's quality of life (QoL) has been established, the associations are complicated by numerous potential mediators and variations in diagnostic criteria. This study was conducted to explore the relationship between OA and QoL and the influence of physical performance, symptoms severity, and psychological factors on this potential relationship using 3 different methods of identification of OA.